2020
DOI: 10.1177/1045389x20905972
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and experimental investigation on wave propagation in the periodic impedance layered structure modulated by magnetorheological fluid

Abstract: This work aims to investigate the elastic wave propagation in the periodic impedance layered structure filled with magnetorheological fluid. The periodic impedance layered structure with high and low impedance layers is constructed by using the magnetorheological fluid with the controllability of liquid–solid conversion. The principle of the periodic impedance layered structure is presented. The transfer model of elastic wave in the proposed structure is established, and the propagation velocity and attenuatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Comparing figures 13 and 12, it can be seen that in these two figures, the overall variation trend of the VLD curve with quasi-periodic impedance distribution patterns is similar, that is, when the number of layers N is 18, the comparison between periodic impedance structure in literature [29] and different quasi-periodic impedance structures demonstrates a similar variation trend with figure 12 (N = 12). This means that when N is 18, there still exist quasi-periodic impedance layered structures whose attenuation effect on vibration is better than that of periodic pattern in a certain frequency ranges.…”
Section: Effects Of Quasi-periodic Impedance Distribution Patterns On...mentioning
confidence: 67%
See 2 more Smart Citations
“…Comparing figures 13 and 12, it can be seen that in these two figures, the overall variation trend of the VLD curve with quasi-periodic impedance distribution patterns is similar, that is, when the number of layers N is 18, the comparison between periodic impedance structure in literature [29] and different quasi-periodic impedance structures demonstrates a similar variation trend with figure 12 (N = 12). This means that when N is 18, there still exist quasi-periodic impedance layered structures whose attenuation effect on vibration is better than that of periodic pattern in a certain frequency ranges.…”
Section: Effects Of Quasi-periodic Impedance Distribution Patterns On...mentioning
confidence: 67%
“…For another, this work further compares the results of different quasi-periodic impedance layered structures with the results obtained from our previous research on periodic impedance structure [29]. When the magnetic induction intensity B is 40 mT, the total number of layers N is 18, the VLD curves of different quasi-periodic impedance layered structures and the results from literature [29] are shown in figure 13.…”
Section: Effects Of Quasi-periodic Impedance Distribution Patterns On...mentioning
confidence: 75%
See 1 more Smart Citation
“…Researchers have recently conducted many studies on the vibration transfer characteristics of MRF. Zhao et al [7] investigated MRF's energy storage and loss modulus under highfrequency excitation. They concluded that the energy storage modulus of MRF increases linearly with frequency.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetorheological (MR) fluid, which consists of carbonyl iron powder and carrier liquid, is a sort of intelligent industrial material [1]. MR fluid exhibits its unique rheological properties, that is, when exposed to an external magnetic field, it can respond quickly within milliseconds and change from the fluid state to a solid-like state, thus generating the shear stress required for work [2][3][4][5]. The shear stress can be reversibly and consecutively adjusted by changing applied current to coordinate the internal magnetic flux density [6].…”
Section: Introductionmentioning
confidence: 99%